2005
DOI: 10.1139/f04-205
|View full text |Cite
|
Sign up to set email alerts
|

Mercury methylation in the hypolimnetic waters of lakes with and without connection to wetlands in northern Wisconsin

Abstract: Rates of Hg methylation and demethylation were measured in anoxic hypolimnetic waters of two pristine Wisconsin lakes using stable isotopes of Hg as tracers. One of the lakes is a clear-water seepage lake situated in sandy terrain with minimal wetland influence. The other is a dark-water lake receiving channelized inputs from a relatively large terrestrial wetland. Methyl mercury (MeHg) accumulated in the anoxic hypolimnia of both lakes during summer stratification, reaching concentrations of 0.8 ng·L–1 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 38 publications
7
49
1
Order By: Relevance
“…Transformations of particle-associated Hg during these transitions are little understood, especially on hour-long or shorter timescales. High methylation rates (Eckley et al, 2005) and methylmercury concentrations (Regnell et al, 1997(Regnell et al, , 2001 have been observed in anoxic hypolimnia, sometimes coinciding with high sulfate reduction rates (Watras et al, 1995). Such findings suggest that changes in Hg speciation at sulfur-bearing redox boundaries can, under some conditions, enhance the propensity for Hg to be methylated on short timescales.…”
Section: Relevant Timescales Of Mercury Reactivitymentioning
confidence: 91%
“…Transformations of particle-associated Hg during these transitions are little understood, especially on hour-long or shorter timescales. High methylation rates (Eckley et al, 2005) and methylmercury concentrations (Regnell et al, 1997(Regnell et al, , 2001 have been observed in anoxic hypolimnia, sometimes coinciding with high sulfate reduction rates (Watras et al, 1995). Such findings suggest that changes in Hg speciation at sulfur-bearing redox boundaries can, under some conditions, enhance the propensity for Hg to be methylated on short timescales.…”
Section: Relevant Timescales Of Mercury Reactivitymentioning
confidence: 91%
“…The balance between methylation and demethylation apparently resets again each spring as a period of renewed meHg accumulation begins below the oxic/anoxic boundary. Spring methylation activity may start in sediments and migrate into the water column as anaerobic microbes move upward toward the source of limiting nutrients, like sulfate and DOC Eckley et al 2005).…”
mentioning
confidence: 99%
“…Suggested values for both methylation and demethylation rates are 10 −5 -10 −2 d −1 [41]. Methylation rate ranged between 0.01 to 0.09 d −1 in a clear lake in Wisconsin [51]. Studies by Carroll et al [52] and Oremland et al [53] Tables 6 and 7.…”
Section: Resultsmentioning
confidence: 99%